"Sumak Kawsay Is Harmful for All of Us": Oil Roads and Well-being among the Waorani in Ecuadorian Amazonia. (May 2021) - Bravo Díaz, Andrea
Exploration of the notion of waponi kewemonipa (living well) among Waorani people living near oil camps suggests that the extractivist developmental model delivered by the Ecuadorian government in the name of buen vivir (living well) is harmful to their experience of well-being. For Waorani living well is related to peace, collective happiness, and certain ecological experiences. The forest, a socio-biological ecological milieu, is the ideal locus of the Waorani conception of living well, but environmental changes related to oil camps and roads challenge their health and vitality. La exploración de la noción de waponi kewemonipa (o buen vivir) entre los waorani que viven cerca de los campamentos petroleros sugiere que el modelo de desarrollo extractivista fomentado por el gobierno ecuatoriano en nombre del "buen vivir" es perjudicial para la experiencia indígena del bienestar. Para los Waorani, vivir bien se relaciona con la paz, la felicidad colectiva y ciertas experiencias de índole ecológico. El bosque, un ambiente socio-biológico, es el locus ideal de la concepción waorani del buen vivir, pero los cambios ecológicos relacionados con los campos petroleros y las carreteras dificulta la experiencia de su salud y vitalidad.